Perangkat Lunak Perhitungan Perubahan Jabatan Dengan Menggunakan Fuzzy Analytical Hierarchy Process (studi kasus : UIN Sunan Ampel Surabaya) - Ilham . (Program Studi Sistem Informasi, 2017)
This study discusses the promotion in an institution by considering many factors, and the submission must be conducted objectively, not subjectively. To be able to give an objective assessment results in every employee by considering all the assessment criteria, one of the methods that can be used is the method of Fuzzy Analytical Hierarchy Process (AHP). From the results of research using Fuzzy Analytical Hierarchy Process method showed that the greatest weight virmansyah discount the value that is equal to 80.78 so a great opportunity to get a change or a promotion. Decision to change positions, it gives the rank order value candidates as a recommendation for promotion to employees. So with the Decision Support System with Analytical Hierarchy Process method can help and facilitate career planning manager (sale or transfer) to save time, costs, and more objective.